Design of constrained-layer damping on plates to sound radiation based on isogeometric analysis and non-negative intensity - Zhang, Xinyan; Xu, Yanming (Frontiers in Physics, 2023)
Non-negative intensity (NNI) is a quantity which avoids near-field cancellation effects in sound intensity and provides direct visualization of the surface contributions to the radiated sound power. Hence, minimizing the integration of NNI on predefined surfaces is implemented to be the design objective of topology optimization for constrained layer damping design on plates in this work. NNI can be easily computed based on the radiation modes and the particle velocity on the surfaces of interest. Regarding the radiation modes, an eigenvalue analysis for the acoustic impedance matrix is required. After evaluating the objective function, the gradients of the objective function are computed by an adjoint variable method. These gradients enable the optimization to be solved by the method of moving asymptotes (MMA). Finally, some numerical examples are presented to validate the proposed optimization approach. Numerical results show that the corner radiation properties of plate can be suppressed by the optimization minimizing the integration of NNI.